Copper(ii) complexes containing enoxacin and heterocyclic ligands: synthesis, crystal structures and their biological perspectives. (14th May 2020) - Kumar, Manish; Kumar, Gyanendra; Masram, Dhanraj T.
Abstract : Two copper-based complexes with a distorted square pyramidal geometry show excellent binding and cleavage affinity towards DNA and proteins. Also, these complexes have potential cytotoxicity against MCF-7 cancer cells. Abstract : In the current study, we synthesized two new copper(ii ) complexes with excellent binding and cleavage affinity towards DNA and proteins. The crystal structure analysis revealed that complexes 1 and 2, which have the general formula [Cu(ENox)bpyCl] and [Cu(phen)2 Cl] (HENox = enoxacin, bpy = 2, 2′-bipyridine and phen = 1, 10-phenanthroline), crystallized in the chiral space groups P 1̄ and C 2/ c with a distorted square pyramidal geometry around the copper atoms ( τ = 0.008 and 0.88), respectively. The biological activity of the complexes towards calf thymus (CT) DNA and proteins (BSA/HSA) was investigated using a series of spectroscopy techniques. All the measurements revealed that both complexes interact with CT DNA via an intercalative mode with excellent binding affinity, where complex 2 exhibited a higher DNA binding constant ( K b ) of 2.87 × 10 5 M −1 . The interaction of these complexes with proteins (BSA/HSA) indicated that they quench the intrinsic fluorescence of proteins in a static quenching mode. Also, the ability of both complexes to cleave supercoiled plasmid DNA (pBR322) and proteins in the presence of an activator such as H2 O2, as revealed by gel-electrophoresis and SDS-PAGE experiments, is consistent with their strong hydrophobic interaction towards proteins. Moreover, molecular docking (MD) analysis on the crystal structures of DNA, BSA and HSA was also performed to measure the ability of the complexes to bind to these target macromolecules. The in vitro cytotoxicity of the complexes was evaluated against breast cancer MCF-7 cells and the results suggested that both complexes exhibit excellent anticancer activity.